What is the ‘Ndrangheta. An analysis from the Anti-Mafia archives (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
Highlights of the depiction of the 'ndrangheta by the Parliamentary Anti-Mafia Committee in 2003 are highlighted below (this is an extract from the annual report). In particular, the characteristics considered specific to the Calabrian mafia (impenetrability, national and international projection, control of territory, etc.) are emphasized, which the reader will find explicated in detail in the document.